HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEAKTIFAN LANSIA MENGIKUTI POSYANDU LANSIA DAN KUALITAS HIDUP - Ria Sugianti; Kristina Everentia Ngasu (Nusantara Hasana Journal, 2021)
Elderly is synonymous with a decline in health status, especially physical health problems. With age, the elderly often experience health problems and various diseases and organ function decline. The declining health condition of the elderly can affect the quality of life and daily activities of the elderly. This study aims to determine the relationship between family support and the activity of the elderly following the posyandu for the elderly and the quality of life. Research Methods using a literature review as a guide to finding research articles obtained from the internet using the Google Scholar site. The results of the analysis of 9 selected research articles showed that family support greatly influenced the level of activity of the elderly in attending the elderly posyandu. because, broadly speaking, the factors that influence the activity of the elderly in participating in posyandu activities are the knowledge of the elderly about the benefits of the posyandu, family support, the motivation of the elderly, and the physical condition of the elderly.